Mental toughness of young football players:differences regarding the age and length of training - Jukic, T.; Mimica, D.; Popeska, B. (2022)
Doing a sport, especially on a professional level, requires high level of sacrifice, motivation, belief, and mental toughness. In this article, we will focus on the latter and try to explain what mental toughness is and why it is important for young athletes. Different stakeholders in the sport point to mental toughness as one of the key characteristics related to individual`s success in the elite sport (Liew et al., 2019). According to Nicholls et al. (2009) developmental factors as age and sport experience can be relevant for mental toughness. Since different studies show diverse relations among those variables, the aim of this research was to examine the mental toughness of young football players and to determine whether players differ in mental toughness with regard to their age and length of training. It was assumed that there were no statistically significant differences in the mental toughness of young football players with regard to players` age and length of training.